Macrophages generated in 3D mechanical microenvironment contribute to recruiting Peritonitis-associated neutrophils in vivo - YanRan Wang; XiaoHang Zou; YuQing Liu; GuoLin Shi; Xiang Li; Xiao Han; Pan Zhang; Hui Yang (Stem Cell Research & Therapy)
Abstract Backgroud The influence of scaffolds with bone marrow (BM) niche-like mechanical properties on the stemness and lineage differentiation of hematopoietic stem cells (HSCs) in vitro has been studied. Previous research has demonstrated that 3D collagen hydrogels can regulate the differentiation trajectory of late myeloid progenitors, leading to the specialization of ‘3D-macrophages’ that express various chemokine genes, including Cxcl2 and Cd14. Comprehensive transcriptional profiles in single-cell level have characterized the interaction between 3D-macrophages and neutrophil clusters through the CXCL2/CXCR2 ligand-receptor binding. Therefore, in this study, we aim to confirm the recruited effect of 3D-macrophage subsets on neutrophils during the immune process. Methods In this study, 3D collagen hydrogels were constructed to culture HSCs in vitro, then CD14+ cells, 3D-macrophages, which generated from HSCs regulated by mechanical microenvironment were purified from 3D gels by using specific antibody CD14 labeling and flow cytometry. First of all, the ability of 3D-macrophages to recruit neutrophils by secreting CXCL2 ligands was investigated in vitro by ELISA and Transwell experiments in vitro. Then, macrophage-deficient mice models were constructed by clodronate liposomes, after 3D-macrophages were transplanted into this models, lipopolysaccharide (LPS) was used to repeat peritonitis to investigate whether 3D-macrophages could recruit neutrophils by secreting CXCL2 ligands and maintain the output of HSCs pool to granulocyte-monocyte progenitor cells (GMPs) pool to sustain the subsequent immune response. Results In vitro experiments show that 3D-macrophages can recruit neutrophils by expressing Cxcl2. The effect of recruitment can also be observed in the peritonitis mice model, where macrophage ablation is experienced, followed by 3D-macrophage transplantation. CD14+ macrophages reach the site of inflammation, not only rescuing the immune deficiency caused by the absence of tissue macrophages but also maintaining the output of the common myeloid progenitor cells (CMPs) pool to the GMPs pool in the BM, thereby maintaining the production of mature immune cells during infection. The study revealed the immune function of macrophage subsets derived from a 3D mechanical microenvironment, which are expected to serve as a potential cell material for clinical significance. Conclusion These results explored the possible immune function of 3D-macrophages derived from 3D gels, assisting in comprehensively understand immune cell interaction in bone marrow hematopoietic microenvironment. Furthermore, 3D-macrophages are expected to serve as a potential cell therapy for immune deficiency caused by the functional deficiency of macrophages.